Policy access to higher education and the dream of haitian diaspora diploma - Bruna Ribeiro Troitinho (Monções, 2019)
The dream of many young Haitians is to migrate to another country to become a diaspora, a Haitian citizen abroad. Alongside this dream, some aim to enter higher education and return to the country with the diploma to help develop the country or even use it symbolically as a distinction about other countrymen. The present research deals with the diploma diaspora, dream pursued by young Haitians who joined the Federal University of Santa Maria from the policy of access to higher education resulting from the agreement with the Sérgio Vieira de Mello Cathedra. From an ethnography carried out between the years 2017 and 2018 with the first students, the research presents how is the insertion of Haitian students in the academic context of UFSM.